Analisis Ketersediaan Dan Pelaksanaan Manajemen Layanan Khusus Di Sd Swasta Angkasa - Abdul Latif B. Sappa; Hiwa Wonda; Putra A. Talomanafe; Marthio Lassi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research aims to analyze the welfare of educators and education personnel, in particular how welfare which includes appreciation, clear promotion paths, and supportive working conditions impacts teacher motivation and performance. The research method uses in-depth interviews to obtain rich and contextual qualitative data from teachers and education personnel. Findings reveal that teachers who feel financially and psychologically prosperous demonstrate high levels of motivation and professionalism, which in turn contributes significantly to the quality of learning. The appreciation given does not only take the form of economic compensation but includes social and professional recognition as well as a transparent and fair career path that encourages teachers to continue developing their abilities. A conducive work environment and continuous training also play an important role in improving teacher welfare and loyalty to educational institutions. The overall research results confirm that teacher welfare is a key factor in creating an effective and sustainable education system. This research recommends improving policies that place teacher welfare as a top priority to improve the quality of national education. These results are supported by the opinions of experts such as Hutasuhut (2025), Sari (2020), and Moleong (2018), who highlight the importance of synergy between compensation, appreciation, and career development in building educator welfare.